Avipedia: An electronic encyclopedia of bird diversity in Baluran National Park - Indonesia - Lina Kumalasari; S. Suhadi; Susriyati Mahanal (Research and Development in Education (RaDEn), 2023)
The development of information technology encourages innovation in the world of education, including in the development of electronic-based learning resources. However, developing electronic encyclopedias based on the diversity of fauna in Indonesia still needs improvement. This research aims to develop an electronic encyclopedia about bird diversity as a source of learning biology. According to the Lee and Owens developing model, this research uses five steps of the developing process. In the final step, the evaluation involved 37 Biology Education Department students at the University of Muhammadiyah Malang with a pretest-posttest group design. Data collection uses validation sheets, pretest-posttest questions, and questionnaires. Pretest and posttest data were analyzed using a gain score to measure its effectiveness in improving student learning outcomes. The effectiveness test results for each indicator item show that the average score for all aspects shows a percentage of 94.7% (very practical). Furthermore, the gain score is 0.47, which indicates that the encyclopedia is feasible, valid, and effective in improving students' cognitive learning outcomes.